Effectiveness of mirror therapy in the motor recovery of upper extremity in the post stroke hemiplegic patients: a randomized controlled trial in a tertiary care hospital in Manipur, Northeast India - Yumnam, Ningthemba; Akoijam, Joy Singh; Singh, Longjam Nilachandra; Oinam, Joymati (International Journal of Advances in Medicine, 2019)
Background: Stroke is a leading cause of disability and majority of the stroke survivors experience upper extremity functional limitations. Therefore, the objective of this study was to evaluate the effectiveness of mirror therapy in addition with a conventional upper limb rehabilitation program in a post stroke hemiplegic patient. Methods: A randomized controlled trial was conducted among 72 post stroke patients aged 35-65 years having hemipa¬resis attending the PMR department, RIMS, Manipur from 2013 to 2016. Assessment was done at baseline, 1 and 6 months for FIM self care, Brunnstrom stages of motor recovery and MAS for spasticity. Both the group participated in a stroke rehabilitation program and study group was given mirror therapy in addition. Descriptive statistics such as mean±SD and inferential statistics like Chi-square test, Student’s t test, and ANOVA were used. A p-value < 0.05 was taken as statistically significant. Results: There was an improvement in Brunnstrom stage and FIM self-care score in both groups, but the post-treatment score was significantly higher in the mirror therapy group. Statistically significant difference in FIM self care and motor recovery between the study and control groups was noted [1.1±0.38 (study) versus 0.88±0.32 (control) for motor recovery and 34.1±2.59 (study) versus 29.5±4.58 (control) for FIM self care]. However, no significant difference was seen in spasticity between the groups. Conclusions: Mirror therapy used in addition to conventional stroke rehabilitation program was found to be effective in the recovery of upper extremity motor functions and daily self care activities in post stroke hemiplegic patients.